Land conversion and urban settlement intentions of the rural population in China: A case study of suburban Nanjing. (February 2016) - Tang, Shuangshuang; Hao, Pu; Huang, Xianjin
Abstract: Rapid urban expansion in China has created a large population of landless farmers. Because these landless farmers are under-compensated for land acquisition and discriminated against by urban institutions, many of them face tremendous difficulties in their urban lives. Consequently, rural citizens generally resist land acquisition and conversion to urban residency. However, given the recent improvements in land compensation standards, the educational qualifications of the rural population and urban employment opportunities, the situation is likely to change. Based on a 2014 survey conducted in Nanjing's suburban Jiangning District, this paper examines the land conversion and settlement intentions of rural citizens under the new circumstances. Both in-depth interviews with local villagers and regression models suggest that relinquishing farmland and housing land and settling in the city are distinct decisions determined by dissimilar factors. The findings suggest that a compensation scheme that integrates rural land requisition and resettlement allocation barely meets the requirements of the affected villagers, which explains the observed resistance of rural citizens to land conversion and urban settlement. Highlights: Both land conversion and settlement intentions of rural citizens are explored. Intentions of rural citizens are examined with respect to the latest circumstances and policy. Farmland conversion, housing land conversion and urban settlement are distinct decisions.